REGIMES OF 110—330 KV SINGLE-CIRCUIT OVERHEAD TRANSMISSION LINES WITH REDUNDANT PHASE - Dmitry Sergeyevich Levin (Advanced Engineering Research)
To improve the performance reliability of the overhead power lines, a redundant phase that can reserve any of the damaged phase conductor, and allow single-phase fusing glaze-ice and rime depositions with conservation of the consumer supply continuity is offered for use. The mode analysis and the subsequent rationale are performed on the basis of the obtained data, the application possibility of the redundant phase for the overhead power lines with 110—330 kV voltage rating without the substantial power quality damage. As a redundant phase, the ground wire with phase conductor parameters and phase insulation is used. It serves to protect overhead circuits from the atmospheric overvoltage in thunderstorm seasons, and as a redundant fourth wire — during the rest of the time. In Matlab (Simulink) program, an electrodynamical simulation model is developed, and the operating regime parameters of the overhead circuit using the fourth wire as a redundant phase are analyzed.